Proposing the Urgency of Consumer Protection Regulations and Freshness Detection Applications for Fish in Traditional Markets Using Technology - Setiawan, Akas Bagus; Firmansyah, Akbar Maulana (Program Studi Manajemen Institut Manajemen Koperasi Indonesia Bandung, 2025)
This study explores consumer knowledge and vendor practices related to the freshness of ikan tongkol (Euthynnus affinis) in traditional markets in Jember, Indonesia. Using a mixed-methods approach, data were collected from 271 consumers and 62 vendors through surveys and interviews. Consumers mostly relied on sensory indicators like color, smell, and texture—especially color—to assess freshness. Although many felt confident in judging freshness, around 20% were uncertain, revealing a knowledge gap. Social media and the Internet were key information sources, raising concerns about accuracy. Vendors commonly used ice storage, with limited access to refrigeration. Interviews highlighted vendor awareness of quality issues but also challenges due to limited infrastructure. The study reveals a mismatch between perceived and actual freshness, shaped by traditional knowledge and limited objective tools. Enhancing education, vendor practices, and introducing simple freshness indicators could improve transparency, safety, and market resilience. The findings offer insights for policy and food system improvements